Chitotriosidase as biomarker for early stage amyotrophic lateral sclerosis: a multicenter study. Issue 3 (3rd April 2021) - Steinacker, Petra; Feneberg, Emily; Halbgebauer, Steffen; Witzel, Simon; Verde, Federico; Oeckl, Patrick; Van Damme, Philip; Gaur, Nayana; Gray, Elizabeth; Grosskreutz, Julian; Jardel, Claude G.; Kachanov, Mykyta; et al.
Abstract: Objective: Levels of chitotriosidase (CHIT1) are increased in the cerebrospinal fluid (CSF) of amyotrophic lateral sclerosis (ALS) patients reflecting microglial activation. Here, we determine the diagnostic and prognostic potential of CHIT1 for early symptomatic ALS. Methods : Overall, 275 patients from 8 European neurological centers were examined. We included ALS with <6 and >6 months from symptom onset, other motoneuron diseases (oMND), ALS mimics (DCon) and non-neurodegenerative controls (Con). CSF CHIT1 levels were analyzed for diagnostic power and association with progression and survival in comparison to the benchmark neurofilament. The 24-bp duplication polymorphism of CHIT1 was analyzed in a subset of patients ( N  = 65). Results: Homozygous CHIT1 duplication mutation carriers (9%) invariably had undetectable CSF CHIT1 levels, while heterozygous carriers had similar levels as patients with wildtype CHIT1 ( p  = 0.414). In both early and late symptomatic ALS CHIT1 levels was increased, did not correlate with patients' progression rates, and was higher in patients diagnosed with higher diagnostic certainty. Neurofilament levels correlated with CHIT1 levels and prevailed over CHIT1 regarding diagnostic performance. Both CHIT1 and neurofilaments were identified as independent predictors of survival in late but not early symptomatic ALS. Evidence is provided that CHIT1 predicts progression in El Escorial diagnostic category in the group of ALS cases with a short duration. Conclusions : CSF CHIT1 level may have additional value in the prognostication of ALS patients with a short history of symptoms classified in diagnostic categories of lower clinical certainty. To fully interpret apparently low CHIT1 levels knowledge of CHIT1 genotype is needed.